003 Whole Body CT scanning for severe blunt multitrauma: analysis of the TARN database 2005–2010. (14th September 2011) - Hunt, P; Lecky, F; Bouamra, O
Abstract : Objectives and Backgrounds: There is growing evidence to recommend the use of "Whole Body" CT (WBCT) scanning in the early management of severe blunt multitrauma patients. A recent study [ Lancet 2009;373 :1455–61] reported a survival advantage with WBCT compared to a non-WBCT approach. We present the results of our analysis of a large retrospective case series taken from the Trauma Audit and Research Network (TARN) database. Methods: We utilised retrospective, multicentre data of severe blunt multitrauma (ISS >15) direct ED admissions aged >15 years recorded in the UK TARN database to compare survival at 30 days between two groups of patients: (1) those who underwent WBCT scans, and (2) those who received a focused CT scan approach as part of their initial management in the Emergency Department. A total of 12 792 cases were included in the final dataset. Results: 2822 (22%) of 12 792 cases underwent WBCT from the ED. The median ISS for the WBCT group was 22 (IQR 14–33) compared to 16 (IQR 9–25) for the focused CT group. The calculated crude mortality rate for the WBCT group was 10.1% compared to 8.7% in the focused CT group (p=0.0124). Multivariate analysis with adjustments for potential confounding factors demonstrated an OR of 1.313 (95% CI 1.083 to 1.592, p=0.006) in favour of survival in the WBCT group. Conclusions: Despite the crude mortality rates appearing to demonstrate a poorer outcome in the WBCT group, correcting for confounding factors revealed an around 30% improvement in survival for the WBCT group. However, when also correcting for the potential effect of clustering, the benefit of WBCT is less clear, with an around 20% improvement in survival and a lower level of significance (p=0.084). Overall, the results of our investigation appear to suggest a potential survival benefit from the use of WBCT in severe blunt multitrauma.